EFFECTIVENESS OF PROBLEM POSING AND INVESTIGATION IN TERMS OF PROBLEM SOLVING ABILITIES, MOTIVATION AND ACHIEVEMENT IN MATHEMATICS - Muzayyanah, Arifah; Wutsqa, Dhoriva Urwatul (Annals of Mathematical Modeling, 2019)
The study aims at describing the comparison between the Problem-Posing Approach and the Investigation Approach in terms of effectiveness from the perspective of Mathematical Problem-Solving Skills, mathematical motivation and Mathematical Learning Achievements. The nature of the study is a quasi-experimental research. During the conduct of the study, the overall number of populations was 206 students from Grade VII of the State 2 Junior High School Gamping. The samples within the study were selected randomly from the population namely 32 students from Grade VII A and 34 students from Grade VII B. Then, the instrument that had been administered within the conduct of the study was the Mathematical Problem-Solving Skills Test, the Mathematical Learning Achievement Test and the Mathematical Learning Motivation Questionnaire. After the data had been gathered, the overall data were analysed by using the one-sample t-test, the T2 Hotteling?s Test and the independent sample t-test. The results of the study show that the learning process by means of Investigation Approach has been more effective in comparison to Problem-Posing Approach from the perspective of Mathematical Problem-Solving Skills and Mathematical Learning Achievement but, on the other hand, the results of the study also show that the learning process by means of Problem-Posing Approach has been more effective in comparison to Investigation Approach from the perspective of Mathematical Learning Motivation for the Grade VII students of the State 2 Junior High School Gamping.